Consumer willingness to pay for Chaiya organic salted egg in smart label packaging: the case study in Surat Thani province - Thongkham, Kanokphorn; Meepianc, Praewwanit; Sukkha, Parichat; Bunmark, Papichaya; Naranram, Phatcharaphon; Phongpharnich, Rapee (Business, Management and Economics Engineering, 2024)
Purpose – This research studies the factors influencing willingness to pay and to evaluate the value of willingness to pay for Chaiya organic salted egg in smart label packaging among consumers in Surat Thani province.Research methodology – The Conjoint Analysis method was used to analyse attribute factors based on literature reviews and related research. Data were collected through interviews and questionnaires from a consumer group aged 15 years and up, totalling 250 individuals.Findings – The results revealed that the attribute of the product with the greatest impact on consumer satisfaction is the certification seal for organic authenticity. This attribute would lead to an increasing price of approximately 1.35 USD per box. If Chaiya organic salted egg have modern packaging with a color bar indicating the salt level and an organic certification seal, the price level of Chaiya organic salted egg was two times higher than general Chaiya organic salted egg. Consumers were willing to pay the highest price at 7.46 USD per box.Research limitations – Having an excessive number of attribute sets may lead to confusion for interviewees when assigning scores to each set of attributes.Practical implications – Conjoint Analysis is a tool suitable for measuring customer satisfaction towards various product attributes and developing new products to introduce into the market.Originality/Value – the attribute of the product with the greatest impact on consumer satisfaction is the certification seal for organic authenticity.